2021
DOI: 10.3390/jcm10102087
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Association of COPD and Asthma with In-Hospital Mortality in Patients with COVID-19. A Systematic Review, Meta-Analysis, and Meta-Regression Analysis

Abstract: Together, chronic obstructive pulmonary disease (COPD) and asthma account for the most common non-infectious respiratory pathologies. Conflicting preliminary studies have shown varied effect for COPD and asthma as prognostic factors for mortality in coronavirus disease 2019 (COVID-19). The aim of this study was to explore the association of COPD and asthma with in-hospital mortality in patients with COVID-19 by systematically reviewing and synthesizing with a meta-analysis the available observational studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 108 publications
5
20
0
1
Order By: Relevance
“…Although asthma has been related to worse outcomes in other viral infections, including other forms of coronavirus ( 16 , 17 ), our analysis did not suggest asthma as a significant risk factor for any of the outcomes measured in this review, apart from mortality (measured as a non-time dependent OR), however sensitivity analysis suggested that the significance of this outcome was subject to the influence of one large study. These results broadly agree with previous meta-analyses that concluded that asthma was not a significant risk factor for either mortality or “severe” health outcomes ( 14 , 18 , 35 , 77 ). When directly comparing reported risks across these meta-analyses, this study's mortality risk is lower (0.83 and 0.93 vs. 0.96 and 1.03) ( 35 , 77 ), which is an expected result given we pooled adjusted ORs and the other meta-analyses were not adjusted for any other covariates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although asthma has been related to worse outcomes in other viral infections, including other forms of coronavirus ( 16 , 17 ), our analysis did not suggest asthma as a significant risk factor for any of the outcomes measured in this review, apart from mortality (measured as a non-time dependent OR), however sensitivity analysis suggested that the significance of this outcome was subject to the influence of one large study. These results broadly agree with previous meta-analyses that concluded that asthma was not a significant risk factor for either mortality or “severe” health outcomes ( 14 , 18 , 35 , 77 ). When directly comparing reported risks across these meta-analyses, this study's mortality risk is lower (0.83 and 0.93 vs. 0.96 and 1.03) ( 35 , 77 ), which is an expected result given we pooled adjusted ORs and the other meta-analyses were not adjusted for any other covariates.…”
Section: Discussionsupporting
confidence: 92%
“…These results broadly agree with previous meta-analyses that concluded that asthma was not a significant risk factor for either mortality or “severe” health outcomes ( 14 , 18 , 35 , 77 ). When directly comparing reported risks across these meta-analyses, this study's mortality risk is lower (0.83 and 0.93 vs. 0.96 and 1.03) ( 35 , 77 ), which is an expected result given we pooled adjusted ORs and the other meta-analyses were not adjusted for any other covariates. These results, however, need to be interpreted with caution as the included studies have used asthma as an umbrella term and did not differentiate between different types or severities of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings correspond to previous studies [29,33], while other studies did not find an association between COPD and in-hospital mortality [34,35]. However, most of the studies, including systematic reviews, only compared the crude rate of COPD between mild or severe COVID-19 disease and did not adjust for other risk factors [12,14]. Patients with COPD frequently have chronic diseases, such as cardiovascular disease, and are older, which are factors known to be associated with unfavorable outcomes of COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the association between asthma and the severity of COVID-19 was not confirmed [2,10,11]. Several meta-analyses that showed an association between asthma or COPD and the risk and consequences of COVID-19 were conducted to overcome the limitations of individual studies [3,[12][13][14]. However, these meta-analyses suffer from substantial heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that low HMGA1 levels may be a risk factor in COVID-19 patients, given the possibility that interactions between SARS-CoV-2 and HMGA1 may impair/trigger inflammatory pathways. Furthermore, it has been demonstrated that low HMGA1 levels in basal stem/progenitor cells of the human airway epithelium are associated with suppression of the expression of genes critical to normal differentiation and up-regulation of genes linked to abnormal differentiation relevant to smoking and chronic obstructive pulmonary disease [90] , which have been demonstrated to be risk factors associated with COVID-19 mortality [72] .…”
Section: Discussionmentioning
confidence: 99%